Sodium butyrate induces mitochondrial pathway apoptosis in liver cancer via ATF4/SLC7A11-mediated ferroptosis - Xiaolan Meng; Yubin Li; Miao He; Chen Wang; Haoran Shengsong; Jiacheng Guo; Jiayu Zhang; Shuang Zhao; Yulei Zhu; Bowen Li; Yuqiang Li; Hongzhi Sun (PLoS ONE, 2026)
Liver cancer, a prevalent and aggressive malignancy globally, is associated with high morbidity and mortality rates. Butyrate, a metabolite produced by intestinal microbiota, is capable of restricting cancer initiation and progression. However, the precise mechanisms underlying its effects on liver cancer remain poorly understood. This study utilized a CCK-8 cytotoxicity assay to demonstrate that sodium butyrate (NaB) suppresses liver cancer cell proliferation through ferroptosis and apoptosis. The involvement of ATF4/SLC7A11 signaling and mitochondrial dysfunction in NaB-induced ferroptosis and apoptosis was further investigated. Results revealed a decrease in ATF4 and SLC7A11 expression, an elevation in the levels of malondialdehyde (MDA) and reactive oxygen species (ROS), and a reduction in glutathione (GSH) in NaB-treated liver cancer cells. These ferroptosis-related alterations could be reversed by an ATF4 activator. Additionally, NaB-treated liver cancer cells presented a decrease in mitochondrial membrane potential (MMP), accumulation of mitochondrial ROS, and mitochondrial damage. These cellular changes disrupted the BAX/BCL-2 balance, leading to cytochrome C release, which subsequently activated caspase9 and caspase3, initiating mitochondrial pathway apoptosis. In vivo , NaB treatment resulted in increased iron content in liver cancer tissues, along with upregulated cytochrome C, activated caspase9, and caspase3 expression; these effects were counteracted by ferrostatin-1 (Fer-1). Collectively, this study elucidates that NaB induces mitochondrial damage via ferroptosis mediated by ATF4/SLC7A11, ultimately triggering mitochondrial pathway apoptosis in hepatoma cells. These findings may offer novel insights into therapeutic strategies for hepatoma.